PEMANFAATAN MEDIA SOSIAL INSTAGRAM SEBAGAI SARANA DIALOG VIRTUAL PIMPINAN DAERAH DENGAN PUBLIK DI KABUPATEN BANYUMAS - Nabila Fatha Zainatul Hayah; Nawawi (AT-TANZIR: JURNAL ILMIAH PRODI KOMUNIKASI PENYIARAN ISLAM, 2023)
Social media is a digital platform that facilitates several needs for social activities in cyberspace. These social activities such as communicating and interacting, or providing information in the form of writing, photos and videos. This makes social media play a role in all lines of life, including in the government sector, namely as a means of public dialogue space between the government and the community. This study aims to study, analyze, and describe the communication carried out by Banyumas Regent Achmad Husain with his community in virtual public spaces on his Instagram account @ir_achmadhusain. This research uses a descriptive qualitative approach aimed at the Banyumas Regent Instagram account @ir_achmadhusain with the content analysis method. Researchers observed the Banyumas Regent's Instagram account and its interactions with the people who followed. The results in this study show that the The Regent of Banyumas made Instagram social media a virtual public dialogue space to accommodate aspirations, input, criticism and suggestions. In addition, Ir. Achmad Husain also uses his Instagram account as a means of public service such as; socialization media, providing education and information as well as virtual interaction spaces between himself and his people.